2019
DOI: 10.3390/jcm8101648
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Moyamoya Disease and RNF213 Mutations on the Spectrum of Plasma Protein and MicroRNA

Abstract: Moyamoya disease (MMD) is a rare cerebrovascular disorder characterized by occlusion of bilateral internal carotid and intracerebral arteries with the compensatory growth of fragile small vessels. MMD patients develop recurrent infarctions in the basal ganglia and subcortical regions. Symptoms include transient ischemic attack or stroke, seizures, and headaches, which may occur suddenly or in a stepwise progression. Mutations in Ring Finger Protein 213 (RNF213), a Zinc ring finger protein, have been identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…MA is frequent in East Asian countries, while rarely reported in Caucasians. The association of MA with genetic disorders, the high familial rate, and the strong linkage with variants of Ring Finger Protein 213 (RNF213)/Mysterin coding gene in East Asian patients strengthen the role of genetic factors in MA pathogenesis [8][9][10][11][12][13][14][15]. Several reports implicated RNF213 as a sensor for mitochondrial dysfunction, hypoxia, and inflammation [14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…MA is frequent in East Asian countries, while rarely reported in Caucasians. The association of MA with genetic disorders, the high familial rate, and the strong linkage with variants of Ring Finger Protein 213 (RNF213)/Mysterin coding gene in East Asian patients strengthen the role of genetic factors in MA pathogenesis [8][9][10][11][12][13][14][15]. Several reports implicated RNF213 as a sensor for mitochondrial dysfunction, hypoxia, and inflammation [14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Anomalies in angiogenesis and vasculogenesis have been invoked as potential disease mechanisms due to the detection of altered levels of cytokines, chemokines, and growth factors in cerebrospinal fluid and sera of MA patients [ 2 , 9 ]. Conversely, the association of MA with genetic disorders, the high familial rate, and the strong association with variants of Ring Finger Protein 213 (RNF213 ) gene in East Asian patients strengthen the role of genetic factors in MA pathogenesis [ 10 , 11 , 12 , 13 , 14 ]. Overall, it is believed that MA results from a complex mechanism in which acquired infectious, inflammatory, and flow dynamic conditions may trigger the disease in genetic susceptible individuals through angiogenic and vasculogenic pathways abnormalities [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cladogram showed that Streptococcaceae and Peptostreptococcaceae were enriched in patients with MMD, while Rhodospirillaceae, Alphaproteobacteria, and Mollicutes were sparse in those patients. It is interesting that increase of Lachnospiraceae (R. gnavus belongs to this family) and decrease of Alphaproteobacteria is caused by angiogenin 21 , which might be associated with upregulated angiogenesis in MMD 22 . Angiogenesis and vasculogenesis manifested in patients with MMD, e.g., basal moyamoya, periventricular anastomosis, and leptomeningeal anastomosis, are regarded as compensation of the stenosis of the main trunk of the internal carotid arteries.…”
Section: Discussionmentioning
confidence: 99%